First insight on the impact of an osteoblastic layer on the bio-tribocorrosion performance of Ti6Al4V hip implants - Runa, M. J.; Mathew, M. T.; Fernandes, Maria Helena; Rocha, Luís Augusto Sousa Marques da [UNESP] (Elsevier B.V., 2015)
In uncemented Ti6Al4V hip implants, the bone-stem interface is subjected to cyclic loading motion driven by the daily activities of the patients, which may lead to the complete failure of the implant in the long term. It may also compromise the proliferation and differentiation processes of osteoblastic cells (bone-forming cells). The main objective of this work is to approach for the first time the role of these organic materials on the bio-tribocorrosion mechanisms of cultured Ti6Al4V alloys. The colonized materials with MG63 osteoblastic-like cells were characterized through cell viability/proliferation and enzymatic activity. Tribocorrosion tests were performed under a reciprocating sliding configuration and low contact pressure. Electrochemical techniques were used to measure the corrosion kinetics of the system, under free potential conditions. All tests were performed at a controlled atmosphere. The morphology and topography of the wear scar were evaluated. The results showed that the presence of an osteoblastic cell layer on the implant surface significantly influences the tribocorrosion behavior of Ti6Al4V alloy. It was concluded that the cellular material was able to form an extra protective layer that inhibits further wear degradation of the alloy and decreases its corrosion tendency.
Keywords: Bio-tribocorrosion; Titanium alloy; Joint replacement; Osteoblast; Biodegradation